Safety and tolerability of Pau d′ Arco (Tabebuia avellanedae) for primary dysmenorrhea: A single-arm, open-label trial on adults ages 18–45. Issue 3 (September 2022) - McClure, C.; Bollen, M.; Buttolph, L.; Stack, E.; Langley, B.O.; Hanes, D.; Wright, K.M.; Tibbitts, D.; Bradley, R.
Abstract: Objectives: To evaluate the safety and tolerability of encapsulated Tabebuia avellanedae in generally healthy women aged 18–45 with primary dysmenorrhea. Methods: A single arm, open-label trial was conducted in which 1050 mg/day of encapsulated Tabebuia avellanedae (Pau d′Arco) was administered to twelve healthy women aged 18–45 for eight weeks. The primary outcome was safety and tolerability as measured by standardized adverse events scales and serial collection of laboratory markers to assess general health, prothrombin times, and the presence or absence of anemia. Secondary outcomes included pain intensity, quality of life, and pain interference measured by the Visual Analog Scale (VAS), the Patient-Reported Outcomes Measurement Information System (PROMIS) 29 survey, and the PROMIS Visual Sexual Function and Satisfaction: Interfering Factors survey, respectively. Exploratory outcomes included serum concentration of high-sensitivity C-reactive protein as a marker of systemic inflammation. Results: Seventy-five percent of participants (n = 9/12) completed the study. Seventy-five percent of study participants (n = 9/12) reported an adverse event, most of which were characterized as mild, and none were determined to be a Food and Drug Administration (FDA) serious adverse event. Most laboratory markers stayed within normal limits throughout the study period with a few clinically mild abnormalities. There was a significant decrease in pain intensity compared to baseline after the first dose (p < .01), after 4 weeks of treatment (p < .01), and after 8 weeks of treatment (p < .01). Over the 8-week intervention period, pain interference, quality of life, and sexual function and satisfaction scores improved nonsignificantly and hs-CRP decreased nonsignificantly. Conclusions: Tabebuia avellanedae supplementation of 1050 mg/day dose for eight weeks in generally healthy women aged 18–45 with primary dysmenorrhea was generally safe, associated with moderate tolerability, and associated with significant improvements in pain intensity scores. Future studies examining the safety and efficacy of Tabebuia avellanedae on primary dysmenorrhea are warranted.